Intestinal Parasitic Infections among School Children. - Ghimire, Gyanendra; Pandeya, Dipendra; Adhikari, Binita; Pradhan, Manoj (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Intestinal parasitic infections are endemic worldwide and constitute a major public health problem and considered as ‘cancers of developing countries. Nepal is small improvised country where 70.0% of morbidity and mortality are associated with infectious diseases. Giardiasis, ascariasis, amoebiasis, ancyclostomiasis and taeniasis are common intestinal parasitic infections in Nepal. Thus, in this paper we report the prevalence of intestinal parasitic infection among school going children of Eastern part of Nepal. Mathods: A total of 300 stool samples were collected from school children of Eastern part of Nepal in random basis. An informed consent was taken from both students and school teachers. The samples were examined for the presence of parasites both macroscopically and microscopically. Standard parasitological examination methods were followed. Results: Out of total 300 school going children included in the study, 195 were male and 105 were female. A total of 97 (29.1%) were positive for one or more parasites. Out of total parasites detected, 35 (36.1%) were protozoan, 39 (40.2%) were helminthes and 23(23.7%) were mixed type. Giardia intestinalis 30 (30.9%) and Hookworm 18 (18.6%) were the commonest protozoan and helminthes respectively. The other parasites detected were A. lumbricoides 15(15.5%), H. nana 6 (6.2%) and Entamoeba histolytica 5(5.2%). Multiple parasitism was detected in 23(23.7%) children. Conclusion: The incidence of intestinal parasite infection was 29%. The commonest infestation was Helminthe. Regular deworming program in association to other preventive measures may help reduce the prevalence. doi: http://dx.doi.org/10.3126/mjsbh.v13i1.12994